SuperCLASS – II. Photometric redshifts and characteristics of spatially resolved μJy radio sources. Issue 2 (2nd April 2020) - Manning, Sinclaire M; Casey, Caitlin M; Hung, Chao-Ling; Battye, Richard; Brown, Michael L; Jackson, Neal; Abdalla, Filipe; Chapman, Scott; Demetroullas, Constantinos; Drew, Patrick; Hales, Christopher A; Harrison, Ian; et al.
ABSTRACT: We present optical and near-infrared imaging covering a ∼1.53 deg 2 region in the Super-Cluster Assisted Shear Survey (SuperCLASS) field, which aims to make the first robust weak lensing measurement at radio wavelengths. We derive photometric redshifts for ≈176 000 sources down to i^′ _AB24 and present photometric redshifts for 1.4 GHz expanded Multi-Element Radio Linked Interferometer Network ( e -MERLIN) and Karl G. Jansky Very Large Array (VLA) detected radio sources found in the central 0.26 deg 2 . We compile an initial catalogue of 149 radio sources brighter than S1.4 > 75 μ Jy and find their photometric redshifts span 0 < z phot < 4 with radio luminosities between 10 21 and 10 25 W Hz −1, with medians of z =0.55 and L_1.4 =1.9× 10^23 W Hz −1, respectively. We find 95 per cent of the μ Jy radio source sample (141/149) have spectral energy distributions (SEDs) best fit by star-forming templates while 5 per cent (8/149) are better fit by active galactic nuclei (AGN). Spectral indices are calculated for sources with radio observations from the VLA and Giant Metrewave Radio Telescope (GMRT) at 325 MHz, with an average spectral slope of α = 0.59 ± 0.04. Using the full photometric redshift catalogue, we construct a density map at the redshift of the known galaxy clusters, z = 0.20 ± 0.08. Four of the five clusters are prominently detected at 7 σ in the density map and we confirm the photometric redshifts are consistent with previously measured spectra from a few galaxies at the cluster centres.